Dynamics of the human bile acid metabolome during weight loss - Schmid, Andreas; Liebisch, Gerhard; Burkhardt, Ralph; Belikan, Hannah; Köhler, Sebastian; Steger, Daniel; Schweitzer, Leonie; Pons-Kühnemann, Jörn; Karrasch, Thomas; Schäffler, Andreas; Justus Liebig University Giessen (My University, 2024)
Bile acids (BA) are supposed to cause metabolic alterations after bariatric surgery (BS). Here we report the longitudinal dynamics of the human BA metabolome by LC–MS/MS after BS versus low calory diet (LCD) in two obesity cohorts over 12 months. Rapid and persistent oscillations of 23 BA subspecies could be identified with highly specific patterns in BS vs. LCD. TCDCA, GLCA, and TLCA represent most promising candidates for drug development.
Keywords: ddc:610